Control of resonance phenomenon in flexible structures via active support - Saleh, AliReza Tavakolpour (2012)
This paper introduces the concept of active support to cope with the resonance phenomenon in the flexible structures. A valid computational platform for the flexible structure was first presented via a finite difference (FD) approach. Then, the active support mechanism was applied to the simulation algorithm through which the performance of the proposed methodology in suppressing the resonance phenomenon was evaluated. The flexible structure was thus excited with the external disturbance and the system response with and without the effect of the active support was investigated through a simulation study. The simulation outcomes clearly demonstrated effective resonance suppression in the flexible structure. Finally, an experimental rig was developed to investigate the validity of the proposed technique. The experimental results revealed an acceptable agreement with the simulation outcomes through which the validity of the proposed control method was affirmed.